2012
DOI: 10.1177/1744259112448181
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance of an insulated roof with reflective insulation: Field tests under hot climatic conditions

Abstract: The use of reflective insulation materials in buildings, for energy saving in summer, has been spreading in southern Europe. These products are not typical of the local building context. There is a lack of well-established measurement systems for reflective insulation thermal transmittance. The aim of this article is to understand whether a reflective insulation material could be effective in hot and temperate climate, also compared with other roof solutions. For this purpose, we compared the thermal performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Numerous studies have been devoted to the problem of energy conservation in building engineering. For example, energy-saving issues of heating the buildings are discussed in [1][2][3][4][5][6][7][8][9]. One of the main ways to reduce heat losses in heating the buildings implies raising RSI-value of building envelope.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have been devoted to the problem of energy conservation in building engineering. For example, energy-saving issues of heating the buildings are discussed in [1][2][3][4][5][6][7][8][9]. One of the main ways to reduce heat losses in heating the buildings implies raising RSI-value of building envelope.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…However, the use of polyethylene in such structures can result in a violation of air exchange and condensate formation. The feasibility of applying heat-reflecting coatings was considered in [2]. At the same time, it is noted that the effectiveness of such coatings largely depends on climatic conditions.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The economic aspect of choosing the thermal protection level of the buildings is under a close attention of specialists [1][2][3][4][5][6][7][8][9][10][11]. Moreover, the economic feasibility of the further increase in the thermal protection level is often questioned [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, reflective roof or insulation coatings have been utilized for increasing the energy savings potential of building envelopes, and several studies can be found in the literature, such as [18,19,[23][24][25][26][27]. Nevertheless, due to the low cost, concrete or ceramic tiles are widely used in roofs in Brazil.…”
Section: Introductionmentioning
confidence: 99%